Parkland : birth of a movement - Cullen, Dave, 1961- (Harper, an imprint of HarperCollinsPublishers, 2019)
Offers an account of the extraordinary teenage survivors of Parkland who became activists and pushed back against the NRA and Congressional leaders, inspiring millions of Americans to join their grassroots #neveragain movement.